Fostering interdisciplinary intercultural citizenship with virtual reality in a world language virtual exchange project - Alice Gruber; Manuela Wagner (Intercultural Communication Education)
Intercultural dialogue is an essential component of intercultural citizenship, i.e., students’ ability to  address complex societal issues. With more interconnected problems comes an increased need for students to communicate and collaborate with people from differing backgrounds. This preliminary study combined the framework of Intercultural Citizenship (ICit) and the United Nations’ Sustainable Development Goals (UN SDGs) with Virtual Reality (VR) and Virtual Exchange (VE) to investigate the students’ development of ICit. Fifteen learners of German, consisting of university students of German in the United States and students studying at a German university, met in dyads or triads in VR over six weeks and worked on their independent projects in which they each addressed a societal environmental problem of their choice. Analyses of the data (pre-project and post-project surveys, weekly journal entries, project presentations) revealed that participants developed their intercultural competence and enhanced their critical language awareness. Some students showed a shift of emphasis: While at the beginning they were more concerned with linguistic elements of the German language toward the end of the project they were focused on the topic of their project. Finally, participants appreciated the VR setting for building relationships, communicating, and developing intercultural competence in an authentic setting.